Framing Strategies for the Populist Coverage: Exploring Press of India and Pakistan - Anbreen Waheed; Dr. Shabir Hussain (Journal of Peace, Development and Communication, 2024)
This research examines media coverage trends during pre-election and post-election periods in Pakistan and India, focusing on newspaper frames, tone, attributes and topics. The analysis is based on data from two prominent newspapers, Dawn and The Hindu, and involves a detailed examination of framing strategies, tone and topic coverage across pre and post phases of the electoral cycle. Findings reveal significant differences in framing approaches between the two newspapers, The research contributes to a deeper understanding of media dynamics and framing strategy processes in India and Pakistan.